Addressing the Impact of COVID-19 on the Early Care and Education Sector - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The COVID-19 pandemic has exacerbated challenges in the early care and education (ECE) sector, including: preexisting structural flaws; insufficient funding mechanisms; sector fragmentation; inadequate support for the workforce; and inequalities, such as the lack of access to high-quality care among low-income, rural populations, and communities of color. Addressing the impacts of the pandemic and the resulting economic recession on the ECE sector will require that state, local, and tribal decision makers use available COVID-19 relief funds to mitigate those impacts while also laying the foundation for longer-term solutions. This rapid expert consultation identifies mitigation strategies that could be implemented to achieve these goals. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats. The National Bureau of Economic Research with the support of the Alfred P. Sloan Foundation commissioned the white papers that informed the development of this rapid expert consultation.

Wastewater-based Disease Surveillance for Public Health Action - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The COVID-19 pandemic spurred a rapid expansion of wastewater-based infectious disease surveillance systems to monitor and anticipate disease trends in communities.The Centers for Disease Control and Prevention (CDC) launched the National Wastewater Surveillance System in September 2020 to help coordinate and build upon those efforts. Produced at the request of CDC, this report reviews the usefulness of community-level wastewater surveillance during the pandemic and assesses its potential value for control and prevention of infectious diseases beyond COVID-19. Wastewater-based Disease Surveillance for Public Health Action concludes that wastewater surveillance is and will continue to be a valuable component of infectious disease management. This report presents a vision for a national wastewater surveillance system that would track multiple pathogens simultaneously and pivot quickly to detect emerging pathogens, and it offers recommendations to ensure that the system is flexible, equitable, and economically sustainable for informing public health actions. The report also recommends approaches to address ethical and privacy concerns and develop a more representative wastewater surveillance system. Predictable and sustained federal funding as well as ongoing coordination and collaboration among many partners will be critical to the effectiveness of efforts moving forward.

Emerging Stronger from COVID-19: Priorities for Health System Transformation - National Academy of Medicine (The National Academies Press, 2023)
In mid-2022, the United States has lost more than 1 million people to the COVID-19 pandemic. We have been real-time witnesses to scores of heroic responses to the disease, death, inequity, and economic strife unleashed by the virus, but have also experienced the consequences of poor pandemic preparedness and long-standing structural failures in our health system. For decades, the U.S. health system has fallen far short of its potential to support and improve individual and population health. The COVID-19 pandemic has presented death and devastation2014but also an unprecedented opportunity to truly transform U.S. health, health care, and health delivery. To capitalize on this opportunity, the National Academy of Medicine gathered field leaders from across all of the major health system sectors to assess how each sector has responded to the pandemic and the opportunities that exist for health system transformation. The opportunity is now to capitalize on the hard-won lessons of COVID-19 and build a health care system that centers patients, families, and communities; cares for clinicians; supports care systems, public health, and biomedical research to perform at the best of their abilities; applies innovations from digital health and quality, safety, and standards organizations; and encourages health care payers and health product manufacturers and innovators to produce products that benefit all.

Evidence-Based Practice for Public Health Emergency Preparedness and Response - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
When communities face complex public health emergencies, state local, tribal, and territorial public health agencies must make difficult decisions regarding how to effectively respond. The public health emergency preparedness and response (PHEPR) system, with its multifaceted mission to prevent, protect against, quickly respond to, and recover from public health emergencies, is inherently complex and encompasses policies, organizations, and programs. Since the events of September 11, 2001, the United States has invested billions of dollars and immeasurable amounts of human capital to develop and enhance public health emergency preparedness and infrastructure to respond to a wide range of public health threats, including infectious diseases, natural disasters, and chemical, biological, radiological, and nuclear events. Despite the investments in research and the growing body of empirical literature on a range of preparedness and response capabilities and functions, there has been no national-level, comprehensive review and grading of evidence for public health emergency preparedness and response practices comparable to those utilized in medicine and other public health fields. Evidence-Based Practice for Public Health Emergency Preparedness and Response reviews the state of the evidence on PHEPR practices and the improvements necessary to move the field forward and to strengthen the PHEPR system. This publication evaluates PHEPR evidence to understand the balance of benefits and harms of PHEPR practices, with a focus on four main areas of PHEPR: engagement with and training of community-based partners to improve the outcomes of at-risk populations after public health emergencies; activation of a public health emergency operations center; communication of public health alerts and guidance to technical audiences during a public health emergency; and implementation of quarantine to reduce the spread of contagious illness.

Exploring the Role of Health Professional Students and Trainees as Members of the Health Workforce During Crises: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The onset of COVID-19 pandemic and inundation of the U.S. health care system emphasized infrastructural and health professional education vulnerabilities. A planning committee of the National Academies of Sciences, Engineering, and Medicine Global Forum on Innovation in Health Professional Education conducted a series of public workshops in the fall of 2021 to explore whether students and trainees should be viewed as members of the health workforce, particular in times of emergency as was experienced during the COVID-19 public health crisis. The planning committee gathered educators, students, administrators, and health professionals to share ideas, experiences, and data to strategize expansion of learning opportunities for medical trainees and enhancement of medical preparedness to unforeseen crises without compromising the quality of patient care. The workshops explored issues such as identifying evidence on value-added roles for students to serve in the delivery of care and in a public health capacity, and balancing the role of learners as consumers (tuition payers) and not licensed providers versus members of the health workforce. This Proceedings highlights presentations and discussions from the workshop.

Systematizing the One Health Approach in Preparedness and Response Efforts for Infectious Disease Outbreaks: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
A planning committee convened by the Forum on Microbial Threats of the National Academies of Sciences, Engineering, and Medicine held a virtual workshop on February 23-25, 2021, titled Systematizing the One Health Approach in Preparedness and Response Efforts for Infectious Disease Outbreaks. The workshop gave particular consideration to research opportunities, multisectoral collaboration mechanisms, community-engagement strategies, educational opportunities, and policies that speakers have found effective in implementing the core capacities and interventions of One Health principles to strengthen national health systems and enhance global health security. This Proceedings of a Workshop summarizes the presentations and discussions of the workshop.

Lessons Learned in Health Professions Education During the COVID-19 Pandemic, Part 2: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The COVID-19 pandemic was arguably the greatest disrupter health professional education (HPE) has ever experienced. To explore how lessons learned from this unprecedented event could inform the future of HPE, the Global Forum on Innovation in Health Professional Education of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop series in 2020 and 2021. The first workshop focused on identifying challenges faced by educators, administrators, and students amidst the pandemic and how the different stakeholder groups shifted and adapted in response. The second workshop explored how experts from various health professions might respond to hypothetical2014but realistic2014future world situations impacting HPE. The final two workshops contemplated the future of HPE post-COVID and explored next steps for applying lessons learned from the workshop series to allow educators to test and evaluate educational innovations in real time. This Proceedings of a Workshop summarizes discussions from the second, third, and fourth workshops in this series.

Long COVID: Examining Long-Term Health Effects of COVID-19 and Implications for the Social Security Administration: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
'Long COVID' refers to the wide range of long-lasting symptoms experienced by some patients after a SARS-CoV-2 infection. The most common symptoms include fatigue, headache, brain fog, shortness of breath, hair loss, and pain. At this time, there are many knowledge gaps related to Long COVID, including the prevalence of the condition, the impact of the symptoms on survivors' ability to function, and the long-term course of the condition. While many individuals with Long COVID recover within one year, others experience little or no decrease in symptom severity over time. Long COVID symptoms can affect a person's ability to work and otherwise function in daily life, so people with the condition may need to utilize programs such as Social Security Disability Insurance (SSDI) and the Supplemental Security Income Program (SSI). The Social Security Administration (SSA), which administers both of these programs, requested that the National Academies of Sciences, Engineering, and Medicine host a public workshop to discuss research into the long-term health effects of COVID-19, their impacts on individuals and populations, and how the SSDI and SSI programs can support individuals who suffer disability as a result of Long COVID. This publication summarizes the presentation and discussion of the workshop.

Mental Health and Substance Use Disorders in the Era of COVID-19: The Impact of the Pandemic on Communities of Color: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The Forum on Mental Health and Substance Use Disorders of the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop, Mental Health and Substance Use Disorders in the Era of COVID-19: With a Special Focus on the Impact of the Pandemic on Communities of Color, on November 23, December 3 and 14, 2020. The workshop featured invited speakers and discussions that addressed how the coronavirus disease 2019 (COVID-19) pandemic has influenced (1) mental health and substance use disorders (SUDs); (2) changes in access to health care and delivery of services for people with mental health disorders and SUDs; and (3) the mental health well-being of the health care workforce - each with a particular focus on the impact of the pandemic on communities of color and how the pandemic has created, revealed, and exacerbated longstanding racial and ethnic disparities in behavioral health care. This Proceedings of a Workshop - in Brief summarizes the presentations and discussions that occurred at the workshop.

School-Based Strategies for Addressing the Mental Health and Well-Being of Youth in the Wake of COVID-19 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
COVID-19, along with heightened racial trauma, has caused unprecedented disruption in the lives of youth aged 10-18, leading them to experience increases in mental health concerns. Addressing these negative impacts requires that education leaders, school districts, state and local decision makers, parents, teachers, and youth work together to ensure that young people have the support and resources needed to address their mental, emotional, and behavioral health needs in the wake of the COVID-19 pandemic. This rapid expert consultation identifies school-based strategies for addressing the mental health and well-being challenges among youth that arose or were exacerbated during the COVID-19 pandemic. Included are strategies designed to support the holistic needs not only of youth but also of educators and staff. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. The associated workshop series that informed the development of this rapid expert consultation was hosted by the National Academies' Forum for Children's Well-Being.

Decarcerating Correctional Facilities during COVID-19: Advancing Health, Equity, and Safety - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The conditions and characteristics of correctional facilities - overcrowded with rapid population turnover, often in old and poorly ventilated structures, a spatially concentrated pattern of releases and admissions in low-income communities of color, and a health care system that is siloed from community public health - accelerates transmission of the novel coronavirus (SARS-CoV-2) responsible for COVID-19. Such conditions increase the risk of coming into contact with the virus for incarcerated people, correctional staff, and their families and communities. Relative to the general public, moreover, incarcerated individuals have a higher prevalence of chronic health conditions such as asthma, hypertension, and cardiovascular disease, making them susceptible to complications should they become infected. Indeed, cumulative COVID-19 case rates among incarcerated people and correctional staff have grown steadily higher than case rates in the general population. Decarcerating Correctional Facilities during COVID-19 offers guidance on efforts to decarcerate, or reduce the incarcerated population, as a response to COIVD-19 pandemic. This report examines best practices for implementing decarceration as a response to the pandemic and the conditions that support safe and successful reentry of those decarcerated.

Rapid Expert Consultation on Critical Federal Capabilities Needed to Evaluate Real-World Safety, Effectiveness, and Equitable Distribution and Use of Medical Countermeasures During a Public Health Emergency - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The COVID-19 pandemic has highlighted the importance of having access to real-world data and evidence to monitor and assess medical countermeasure (MCM) use and performance so policy makers can make more effective and rapid public health decisions, protect population health, and save lives. During public health emergencies, the use of MCMs, such as therapeutics, vaccines, and diagnostics, can be made available to the public under a range of regulatory access mechanisms. This Rapid Expert Consultation was produced by individual members of the Standing Committee for CDC Center for Preparedness and Response. Its aim is to review and propose modifications to an initial draft list of critical federal capabilities presented by the Centers for Disease Control and Prevention and the U.S. Food and Drug Administration that are needed to evaluate real-world safety, effectiveness, equitable distribution, access, and use of MCMs during a public health emergency. This effort draws from expert input, published literature, and lessons learned from previous public health emergencies, as well as the ongoing COVID-19 pandemic.

Rapid Expert Consultation on Social Distancing for the COVID-19 Pandemic (March 19, 2020) - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
This rapid expert consultation responds to a request from the Office of Science and Technology Policy (OSTP) concerning the effectiveness and costs of social distancing measures in contending with COVID-19. The National Academies of Sciences, Engineering, and Medicine convened a standing committee of experts to help inform OSTP on critical science and policy issues related to emerging infectious diseases and other public health threats. The standing committee includes members with expertise in emerging infectious diseases, public health, public health preparedness and response, biological sciences, clinical care and crisis standards of care, risk communication, and regulatory issues.

Rapid Expert Consultations on the COVID-19 Pandemic: March 14, 2020-April 8, 2020 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
In response to a request from the Office of Science and Technology Policy and the Office of the Assistant Secretary for Preparedness and Response, the National Academies of Sciences, Engineering, and Medicine convened a standing committee of experts to help inform the federal government on critical science and policy issues related to emerging infectious diseases and other 21st century health threats. This set of Rapid Expert Consultations are the first of their kind and represent the best evidence available to the Committee at the time each publication was released. The science on these issues is continually evolving, and the scientific consensus the Committee reaches on these topics will likely evolve with it. The standing committee includes members with expertise in emerging infectious diseases, public health, public health preparedness and response, biological sciences, clinical care and crisis standards of care, risk communication, and regulatory issues.

Rapid Expert Consultation on Crisis Standards of Care for the COVID-19 Pandemic (March 28, 2020) - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
This rapid expert consultation responds to a request from the Office of Science and Technology Policy (OSTP) concerning the implementation of crisis standards of care (CSC) in response to the COVID-19 outbreak. Building on a 10-year foundation of work by the Institute of Medicine, this document summarizes the broad principles and core elements of CSC planning and implementation. The National Academies of Sciences, Engineering, and Medicine convened a standing committee of experts to help inform OSTP on critical science and policy issues related to emerging infectious diseases and other public health threats. The standing committee includes members with expertise in emerging infectious diseases, public health, public health preparedness and response, biological sciences, clinical care and crisis standards of care, risk communication, and regulatory issues.

Global Health Risk Framework: Governance for Global Health: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak. In order to explore the potential for improving international management and response to outbreaks the National Academy of Medicine agreed to manage an international, independent, evidence-based, authoritative, multistakeholder expert commission. As part of this effort, the Institute of Medicine convened four workshops in summer of 2015 to inform the commission report. The presentations and discussions from the Governance for Global Health Workshop are summarized in this report.

Global Health Risk Framework: Resilient and Sustainable Health Systems to Respond to Global Infectious Disease Outbreaks: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak. In order to explore the potential for improving international management and response to outbreaks the National Academy of Medicine agreed to manage an international, independent, evidence-based, authoritative, multistakeholder expert commission. As part of this effort, the Institute of Medicine convened four workshops in summer of 2015 to inform the commission report. The presentations and discussions from the Workshop on Resilient and Sustainable Health Systems to Respond to Global Infectious Disease Outbreaks are summarized in this report.

Engaging the Private-Sector Health Care System in Building Capacity to Respond to Threats to the Public's Health and National Security: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Disasters tend to cross political, jurisdictional, functional, and geographic boundaries. As a result, disasters often require responses from multiple levels of government and multiple organizations in the public and private sectors. This means that public and private organizations that normally operate independently must work together to mount an effective disaster response. To identify and understand approaches to aligning health care system incentives with the American public's need for a health care system that is prepared to manage acutely ill and injured patients during a disaster, public health emergency, or other mass casualty event, the National Academies of Sciences, Engineering, and Medicine hosted a 2-day public workshop on March 20 and 21, 2018. This publication summarizes the presentations and discussions from the workshop.

Reusable Elastomeric Respirators in Health Care: Considerations for Routine and Surge Use - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Protecting the health and safety of health care workers is vital to the health of each of us. Preparing for and responding to a future influenza pandemic or to a sustained outbreak of an airborne transmissible disease requires a high-level commitment to respiratory protection for health care workers across the wide range of settings in which they work and the jobs that they perform. Keeping health care workers healthy is an ethical commitment both in terms of addressing the occupational risks faced by health care workers and of providing for the continuity of patient care and services needed to maintain the health of individuals and communities. During a public health emergency, challenges will arise concerning the availability of respiratory protective devices (i.e., respirators). Reusable respirators (specifically, reusable half-facepiece elastomeric respirators) are the standard respiratory protection device used in many industries, and they provide an option for use in health care that has to date not been fully explored. The durability and reusability of elastomeric respirators make them desirable for stockpiling for emergencies, where the need for large volumes of respirators can be anticipated. However, they are used infrequently in health care. Reusable Elastomeric Respirators in Health Care explores the potential for the use of elastomeric respirators in the U.S. health care system with a focus on the economic, policy, and implementation challenges and opportunities. This report examines the practicability of elastomeric use in health care on a routine basis and during an influenza pandemic or other large aerosol-transmissible outbreak, when demand for respiratory protective devices by U.S. health care personnel may be larger than domestic supplies. The report also addresses the issues regarding emergency stockpile management of elastomeric respiratory protective devices.

Emerging Viral Diseases: The One Health Connection: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In the past half century, deadly disease outbreaks caused by novel viruses of animal origin - Nipah virus in Malaysia, Hendra virus in Australia, Hantavirus in the United States, Ebola virus in Africa, along with HIV (human immunodeficiency virus), several influenza subtypes, and the SARS (sudden acute respiratory syndrome) and MERS (Middle East respiratory syndrome) coronaviruses - have underscored the urgency of understanding factors influencing viral disease emergence and spread. Emerging Viral Diseases is the summary of a public workshop hosted in March 2014 to examine factors driving the appearance, establishment, and spread of emerging, re-emerging and novel viral diseases; the global health and economic impacts of recently emerging and novel viral diseases in humans; and the scientific and policy approaches to improving domestic and international capacity to detect and respond to global outbreaks of infectious disease. This report is a record of the presentations and discussion of the event.